AN IN-DEPTH EXPLORATION OF EMPIRICAL RESEARCH ON ENTREPRENEURIAL MINDFULNESS: A SYSTEMATIC LITERATURE REVIEW TO EXPLORE NUANCES, FINDINGS, AND CHALLENGES - Zaenal Aripin; Nurhaeni Sikki; Raden Roro Fatmasari (Organisasi Kreatif Indonesia Emas, 2024)
Entrepreneurial spirit can drive a person's success. By having an entrepreneurial spirit, someone will always be active in creating and developing a business, so that many jobs can help the Indonesian nation in alleviating unemployment and poverty. This research uses literature study research with a qualitative approach. The result of this research is that Entrepreneurship is the process of creating something new at the value of using the necessary time and effort, bearing physical risks as well as accompanying social risks, receiving the resulting monetary rewards, meeting needs, and desires through innovation. Someone does entrepreneurship for several reasons, namely financial reasons; Social reasons; Reasons for Service and Reasons for Self-Fulfillment It is not uncommon for someone to be entrepreneurial as well as a form of fulfillment of satisfaction or achievement of themselves. The challenges of entrepreneurship are uncertain income; Losses due to loss of investment capital; It takes hard work and a long time; The quality of life remains low despite steady efforts.